Taxonomy and biogeography of living species of the Family Notorotaliidae (Notorotalia, Parrellina, Porosorotalia, Buccella, Cristatavultus) - Hayward, B. W.; Holzmann, M.; Pawlowski, J.; Wollenburg, J.; Majewski, W. (Micropaleontology, 2023)
DNA sequencing shows that species of the genera Notorotalia, Porosorotalia and Buccella form a distinct branch (Notorotaliidae) of Rotaloidea, and cluster as sister to Elphidiidae. In this review we report on the sequencing of three species of Buccella (from the Arctic Ocean, Patagonia and Chile) and one each of Notorotalia (New Zealand) and Porosorotalia (Chile). This information has been combined with all the morphological descriptive information on species of these genera plus the genera Cristatavultus and Parrellina to provide a global synthesis of living species of the Notorotaliidae. We recognize 11 species of the southern hemisphere genus Notorotalia, which has a centre of diversity around New Zealand (8 species). A second southern-hemisphere-restricted genus, restricted to eastern Australia is Parrellina (3 species) although specimens (possibly introduced) have been recorded from the Mediterranean Sea. Cristatavultus has a single species, with a tropical west Pacific distribution.We synonymize Cribrorotalia under Porosorotalia, which has a disjunct distribution with one species in the northwest Pacific and a second around the southern parts of South America. Buccella is the most diverse and widespread genus (16 species recognized) with its greatest abundance in the Arctic Ocean and around subantarctic-temperate South America. Five species of Buccella live in a belt along the west coast of central America, from USAto Peru, with some spillage into the Caribbean Sea and Gulf of Mexico. Two new species of Buccella are recognized: B. dejardini (from South Georgia) and Buccella n. sp. A (from Chile).